2004
DOI: 10.1530/eje.0.151s081
|View full text |Cite
|
Sign up to set email alerts
|

GH improves growth and clinical status in children with cystic fibrosis -- a review of published studies

Abstract: Children with cystic fibrosis (CF) have problems with poor linear growth and inadequate weight gain. Nutritional augmentation has been the mainstay of therapy for improving both weight and height in CF; however, inadequate growth continues to be a problem. Furthermore, protein catabolism has been documented even in non-acutely ill adults and children with CF, and could adversely affect longitudinal growth. Human recombinant GH has positive effects on nitrogen balance, and multiple studies have demonstrated imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 33 publications
0
32
0
2
Order By: Relevance
“…(2003) showed that growth parameters at age 3 positively predict lung function at age 6 in CF patients (3). Further evidence that growth stimulation is beneficial to CF patients is that treatment with GH not only stimulates growth and elevates serum Igf-1 levels, but may also improve clinical status (5). For example, a randomized, controlled trial found that administration of GH to CF patients improves clinical status as measured by lung capacity and reduced hospital visits (4).…”
Section: Growth In Cystic Fibrosis Micementioning
confidence: 99%
See 2 more Smart Citations
“…(2003) showed that growth parameters at age 3 positively predict lung function at age 6 in CF patients (3). Further evidence that growth stimulation is beneficial to CF patients is that treatment with GH not only stimulates growth and elevates serum Igf-1 levels, but may also improve clinical status (5). For example, a randomized, controlled trial found that administration of GH to CF patients improves clinical status as measured by lung capacity and reduced hospital visits (4).…”
Section: Growth In Cystic Fibrosis Micementioning
confidence: 99%
“…For example, a randomized, controlled trial found that administration of GH to CF patients improves clinical status as measured by lung capacity and reduced hospital visits (4). It is suggested that the beneficial effects of growth hormone may be attributed to increased respiratory muscle strength and larger absolute lung capacity (5).…”
Section: Growth In Cystic Fibrosis Micementioning
confidence: 99%
See 1 more Smart Citation
“…The dominant clinical features are chronic lung disease and pancreatic insufficiency with poor nutrition and growth. 3,4 Treatment advances in CF over the past 25 years have improved measures of nutrition, pulmonary function, and mortality. The median age of survival has improved consistently from 1955 to the most recent data in 2008.…”
mentioning
confidence: 99%
“…O processo inflamatório crônico tanto afeta a produção e a secreção do hormônio de crescimento (GH) como inibe o crescimento em nível tecidual (7,8). Dessa maneira, na FC, a suplementação nutricional isolada pode ser insuficiente para ocasionar a recuperação adequada do peso e da estatura.…”
Section: Introductionunclassified